Pengaruh Metode Pembelajaran Curah Pendapat (Brainstorming) dan Minat Belajar Terhadap Hasil Belajar Ekonomi Siswa Kelas X di MAN 2 Batusangkar Kabupaten Tanah Datar - Alhusna Nupiah (Departement of Mathematics Education, 2023)
The research purposes to investigate the impact of the students who teach by using Brainstorming Method and Variety Lecturing Method with the student’s interest at study toward the result of their study on economics subject in MAN 2 Batusangkar. The research is quasy experimental research by using two classes. The population of this research is the students grade X at MAN 2 Batusangkar. The type of sample is cluster and the students X-is3 as the class experiment and class X-is1 as control class. This research using analysis descriptive and inductive analysis by using two-ways of ANOVA. The results showed: (1) There is significant result of the students who got treatment by Brainstorming Method than the students who thought by using Variety Lecturing Method, (2) There is significant result of the students who have good interest in study by using Brainstorming Method than the students who have high interest thought by using Variety Lecturing Method, (3) There is significant result of the students who have low interest in study by using Brainstorming Method in fresh grade, (4)There is no interaction between the use of Brainstorming method and the student’s interest toward the result of their study of fresh grade. After conducted this research, the researcher would like to propose suggestion to the teacher to explore applying Brainstorming Method to increase their student interest in study.